Phylogenetic Analysis of Feline Coronavirus Strains in an Epizootic Outbreak of Feline Infectious Peritonitis. (20th March 2013) - Barker, E.N.; Tasker, S.; Gruffydd‐Jones, T.J.; Tuplin, C.K.; Burton, K.; Porter, E.; Day, M.J.; Harley, R.; Fews, D.; Helps, C.R.; Siddell, S.G.
<x xml:space="preserve">Abstract</x> Background Feline coronavirus (FCoV) infection is common. In a small percentage of cats, FCoV infection is associated with the fatal disease feline infectious peritonitis (FIP). Genetically distinct virulent and avirulent strains of FCoV might coexist within a cat population. Objectives To determine whether the strains of FCoV in FIP‐affected cats are closely related or genetically distinct from the fecally derived strains of FCoV in contemporary‐asymptomatic cats during an epizootic outbreak of FIP. Animals Four cats euthanized because of FIP and 16 asymptomatic cats. Methods This prospective outbreak investigation was initiated during an outbreak of FIP in cats within or rehomed from a rescue/rehoming center. Postmortem samples were collected from cats with FIP and contemporaneous fecal samples from asymptomatic cats. RNA was purified from tissue and fecal samples, FCoV gene fragments were reverse transcribed, PCR‐amplified using novel primers, and sequenced. Sequences were aligned with ClustalW and compared with published FCoV sequences. Results FCoV RNA was detected in all 4 FIP cat postmortem samples and in 9 of the 16 fecal samples from contemporary‐asymptomatic cats. Novel primers successfully amplified fragments from 4 regions of the genome for all FCoV‐positive samples. Phylogenetic analysis showed that the FIP‐associated strains of FCoV from the outbreak were very closely related to the fecally derived strains of FCoV from contemporary‐asymptomatic cats. Conclusions and Clinical Importance Sequence analysis provided no evidence that genetically distinct virulent and avirulent strains of FCoV were present during this FIP outbreak.